Antihypertension Nanoblockers Increase Intratumoral Perfusion of Sequential Cytotoxic Nanoparticles to Enhance Chemotherapy Efficacy against Pancreatic Cancer. Issue 29 (26th August 2022) - Bian, Suchen; Dong, Haijiang; Zhao, Long; Li, Zequn; Chen, Jian; Zhu, Xingxin; Qiu, Nasha; Jia, Xing; Song, Wenfeng; Li, Zekuan; Zheng, Shusen; Wang, Hangxiang; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC), one of the worst prognosis types of tumors, is characterized by dense extracellular matrix, which compresses tumor vessels and forms a physical barrier to inhibit therapeutic drug penetration and efficacy. Herein, losartan, an antihypertension agent, is applied as a tumor stroma modulator and developed into a nanosystem. A series of lipophilic losartan prodrugs are constructed by esterification of the hydroxyl group on losartan to fatty acids. Based on the self‐assembly ability and hydrodynamic diameter, the losartan‐linoleic acid conjugate is selected for further investigation. To improve the stability in vivo, nanoassemblies are refined with PEGylation to form losartan nanoblocker (Los NB), and administered via intravenous injection for experiments. On murine models of pancreatic cancer, Los NB shows a greater ability to remodel the tumor microenvironment than free losartan, including stromal depletion, vessel perfusion increase, and hypoxia relief. Furthermore, Los NB pretreatment remarkably enhances the accumulation and penetration of 7‐ethyl‐10‐hydroxycamptothecin (SN38)‐loaded nanodrugs (SN38 NPs) in tumor tissues. Expectedly, overall therapeutic efficacy of SN38 NPs is significantly enhanced after Los NB pretreatment. Since losartan is one of the most commonly used antihypertension agents, this study may provide a potential for clinical transformation in stroma‐rich PDAC treatment. Abstract : Self‐assembled antihypertension losartan (Los)‐fatty acid prodrugs are constructed. Los‐linoleic acid conjugate is chosen and PEGylated to afford Los nanoblocker (NB). In the pancreatic cancer mouse model, intravenously injected Los NB remodels stromal tumor microenvironment, improves the intratumoral accumulation and penetration of sequentially administered cytotoxic 7‐ethyl‐10‐hydroxycamptothecin (SN38) nanotherapy, and results in the superior antitumor activity.